2022
DOI: 10.1016/j.celrep.2022.110332
|View full text |Cite
|
Sign up to set email alerts
|

Bivalent-histone-marked immediate-early gene regulation is vital for VEGF-responsive angiogenesis

Abstract: Highlights d Specific bivalent gene body signature regulates VEGFresponsive angiogenic acute TFs d Non-canonical PRC1.3 transiently transactivates PRC2enriched angiogenic genes d VEGF-NFAT-associated epigenome modifier PTIP directs NFAT-targeted gene activation d Reductions in PRC1.3 or PTIP lead to impaired postnatal angiogenesis

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 50 publications
0
12
0
Order By: Relevance
“…VEGF mediates immediate (within 1 h) gene responses on a genome-wide scale. 26 NFAT and the downstream early growth response factor transactivate early angiogenic or inflammatory responses in ECs. 27 In contrast, FOXO1 mainly regulates expression of late response proteins in VEGF-treated ECs.…”
Section: Resultsmentioning
confidence: 99%
“…VEGF mediates immediate (within 1 h) gene responses on a genome-wide scale. 26 NFAT and the downstream early growth response factor transactivate early angiogenic or inflammatory responses in ECs. 27 In contrast, FOXO1 mainly regulates expression of late response proteins in VEGF-treated ECs.…”
Section: Resultsmentioning
confidence: 99%
“…It is unclear why Apold1 does not affect developmental angiogenesis while strongly restricting angiogenesis in several pathological settings. We showed that Apold1 expression is activated by VEGF, which is known to activate an immediate early gene response [62], as well as by hypoxia. A previous RNAseq screen already identified Apold1 to be part of a HIF-dependent angiogenic response downstream of YAP/TAZ in bone ECs [53].…”
Section: Discussionmentioning
confidence: 93%
“…Transient induction of immediate- early genes by vascular endothelial cell growth factor in human umbilical vein endothelial cells occurs through the activation of their bivalent (H3K4me3 and H3K27me3 positive [(90)]) promoters whilst H3K27me3 is maintained and EZH2 accumulates at the promoter. cPRC1 then deposits H2AK119ub1, coinciding with the reduction in gene expression (91). The sense-strand promoter shares several functional features with immediate-early genes, including bivalent promoter histone marks (26; 28; 29), independence from de novo protein synthesis for reactivation (27) and responsiveness to p38-MAPK signaling (27).…”
Section: Discussionmentioning
confidence: 99%
“…The sense-strand promoter shares several functional features with immediate-early genes, including bivalent promoter histone marks (26; 28; 29), independence from de novo protein synthesis for reactivation (27) and responsiveness to p38-MAPK signaling (27). Whilst it is tempting to draw parallels between these systems, the immediate-early gene response studied by (91) is far more short- lived ( < 4 hrs. ), with transcript levels falling by 60 minutes post-stimulation.…”
Section: Discussionmentioning
confidence: 99%